G204(P) Two year outcome of infants born ≥32 weeks gestation and ≤1500g. (May 2019) - Sikka, G; Allman, A; Evans, J; Sharma, A; Goel, N; Banerjee, S; Kenny, C
Abstract : Aims: It is a BAPM recommendation that infants with a birth weight of ≤1500 g have a standardised neurodevelopmental outcome assessment at a corrected age of 2 years. Having noted morbidity in this group as assessed using various neurodevelopment scales in a single centre, we reviewed all available data from three tertiary care NICUs over an extended geographical area and over a longer time period for this cohort. Methods: Data on infants born at ≥32 weeks gestation with birth weight ≤1500 g, who were admitted to one of the three tertiary NICUs during a defined period of time and survived to discharge, were retrieved from neonatal databases. The three centres follow up the high risk infants with a standardised neuro-developmental assessment using the Bayley Scales of Infant and Toddler Development–Third Edition (Bayley-III). The results of the 2 year outcomes were analysed. Results: Between 2006 and 2016, 230 babies (born at ≥32 completed weeks gestation and birth weight ≤1500 g) were admitted to 1 of the 3 tertiary units; 228 (99.1%) survived to discharge. Fourteen babies (6.1%) were born at gestation ≥36 weeks. The mean gestational age was 32.5 weeks. The total number of deaths between discharge and 2 years of age was 1 (0.9%). Two year outcomes were available for 138 (60%) of these infants. Fifty infants (36%) had documented neurodevelopmental problems, including moderate disability in 15 (10.8%) and severe disability in 16 (11.5%) in at least one of the domains assessed by Bayley-III. Cerebral palsy was diagnosed in 4 babies (2.8%). Sixteen infants (11.5%) had moderate and 14 (10.1%) had severe delay in speech and language. Visual impairment was seen in 2 babies (1.4%) and hearing impairment in 2 (1.4%) babies. Conclusion: Preterm small for gestational age and growth restricted infants are known to be at increased risk of neurodevelopmental morbidity compared with their normally grown counterparts. Our study demonstrates a high level of disability in this group, with speech and language delay being the most commonly affected domain. This group of infants should be considered for early targeted intervention.